A beta‐complex statistical four body contact potential combined with a hydrogen bond statistical potential recognizes the correct native structure from protein decoy sets. Issue 8 (1st June 2013) - Sánchez‐González, Gilberto; Kim, Jae‐Kwan; Kim, Deok‐Soo; Garduño‐Juárez, Ramón
ABSTRACT: We present a new four‐body knowledge‐based potential for recognizing the native state of proteins from their misfolded states. This potential was extracted from a large set of protein structures determined by X‐ray crystallography using BetaMol, a software based on the recent theory of the beta‐complex (β‐complex) and quasi‐triangulation of the Voronoi diagram of spheres. This geometric construct reflects the size difference among atoms in their full Euclidean metric; property not accounted for in a typical 3D Delaunay triangulation. The ability of this potential to identify the native conformation over a large set of decoys was evaluated. Experiments show that this potential outperforms a potential constructed with a classical Delaunay triangulation in decoy discrimination tests. The addition of a statistical hydrogen bond potential to our four‐body potential allows a significant improvement in the decoy discrimination, in such a way that we are able to predict successfully the native structure in 90% of cases. Proteins 2013; 81:1420–1433. © 2013 Wiley Periodicals, Inc.